Translation and Loss-Aversion - Goldfajn, Tal (TTR)

(untitled) (Association canadienne de traductologie, 2020)
This paper is about the inflation of loss talk in a certain discourse on translation and how translation is often presented as a disaster or even an emblem of what is always missing. My guiding questions will be: Why has the notion of loss become such a dominant concept when talking about translation? Where does this rhetoric of loss—in translators’ reflections, in translation reviews as well as in scholarly material of theoreticians—come from? What are some of the assumptions that underlie this loss discourse on translation products? Can we go beyond a descriptive perspective of the phenomenon and try to come up with a few explanations for this loss talk on translation? I shall furthermore explore the concept of loss-aversion from economics and decision theory (Kahneman, 2011), and argue that loss-aversion may help us to better understand how the notion of loss, and more generally the gain-loss equation, operate in the field of translation. Finally looking at translation discourse through the losing-glass, I will briefly discuss a few “unlosables” from the field of biblical Hebrew translation.